2015
DOI: 10.6090/jarq.49.59
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Meteorological Measurements made over Three Rainy Seasons and Rainfall Simulations in Sinazongwe District, Southern Province, Zambia

Abstract: Zambia has frequently been affected by abnormal weather and droughts. Our research focused on the type of meteorological data required to assist farmers' efforts to avoid the risks associated with these weather conditions. We conducted local meteorological observations from September 2007 to August 2010 at three sites in Sinazongwe District, Zambia. The three rainy seasons of this period coincided in sequence with La Niña (normal) and El Niño conditions. The mean annual precipitation for the three years of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The role of surface heating is indicated by the lag of about 2 to 4 h between the peak in temperatures and the peak in area average rainfall. Kanno et al [18] also found a strong diurnal cycle in the rainfall of Zambia, indicating strong afternoon convection, and large spatial differences in sites that they studied due to differences in topography.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The role of surface heating is indicated by the lag of about 2 to 4 h between the peak in temperatures and the peak in area average rainfall. Kanno et al [18] also found a strong diurnal cycle in the rainfall of Zambia, indicating strong afternoon convection, and large spatial differences in sites that they studied due to differences in topography.…”
Section: Discussionmentioning
confidence: 92%
“…Our study also points to a clear need for more ground observations that would greatly assist studies on the performances of different model configurations, not least because the reanalysis and satellite estimates gave some contrasting results. Kanno et al [18] also concluded that the existing meteorological stations were too sparse to use for local meteorological studies. In their situational analysis Venäläinen et al [4] recommended an increase in the number of ground observations and procurement of a radar system and a lightning detection system for ZMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Africa, crop yields have been shown to correlate with ENSO events with El Niño having a negative impact on millet and a positive impact on maize and sorghum production with an indirect effect on temperature and rainfall during the short planting period in the Sahel [30]. Warm ENSO events in east Africa were found to coincide with drier conditions affecting surface temperatures and the Normalized Difference Vegetation Index (NDVI), while Pacific SST anomalies tend to affect air temperature in east Africa, according to Plisnier et al [31], ENSO has been shown to be responsible for variations in temperature, wind, and humidity in Zambia, with three rainy seasons corresponding to La Niña, normal, and El Niño conditions [32].…”
Section: Literature Reviewmentioning
confidence: 96%